Pengaruh Kualitas Pelayanan terhadap Kepuasan Konsumen Pengguna Jasa J&T Express Sibuhuan Kecamatan Barumun Kabupaten Palas - Syafitri Daulay Nur; Mufti Fahrizal; Sari Fitri (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
The Influence of Service Quality on Consumer Satisfaction of J&T Express Sibuhuan Service Users, Padang Lawas Regency. This study aims to determine whether there is an influence of service quality on consumer satisfaction among J&T Express Sibuhuan users. The research was conducted with service quality as the independent variable and consumer satisfaction as the dependent variable. Using a quantitative approach, the study involved a population of 150,474 and a sample of 100 respondents. The sampling technique employed was purposive sampling, and data were collected through questionnaires. The analysis utilized SPSS version 21 for validity, reliability, normality, heteroscedasticity tests, simple linear regression, partial tests (t-tests), and determination tests. The findings indicate that service quality has a significant positive effect on consumer satisfaction, with a t-value of 2.272, exceeding the t-table value of 1.661 and a significance level of 0.000 (p < 0.05). The coefficient of determination is 0.350, suggesting that service quality influences consumer satisfaction by 35%.